The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/hbm.24638
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter T1‐w/T2‐w ratios are higher in Alzheimer's disease

Abstract: Myelin determines the conduction of neuronal signals along axonal connections in networks of the brain. Loss of myelin integrity in neuronal circuits might result in cognitive decline in Alzheimer's disease (AD). Recently, the ratio of T1‐weighted by T2‐weighted MRI has been used as a proxy for myelin content in gray matter of the cortex. With this approach, we investigated whether AD dementia patients show lower cortical myelin content (i.e., a lower T1‐w/T2‐w ratio value). We selected structural T1‐w and T2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 77 publications
8
31
0
Order By: Relevance
“…This is a finding consistent with converging evidence that AD involves a remyelination process in the gray matter as a homeostatic response to myelin breakdown [23]. There have been in vivo and ex vivo findings of increased intracortical myelin content [24–26] and disorganized myeloarchitecture [24, 27] in AD patients compared to normal controls. The studies have further noted a visibly inhomogeneous band of hypointense T2*‐weighted MRI signals across the cortex, which blurred the cortical laminae and was highly associated with myelin content.…”
Section: Discussionsupporting
confidence: 83%
“…This is a finding consistent with converging evidence that AD involves a remyelination process in the gray matter as a homeostatic response to myelin breakdown [23]. There have been in vivo and ex vivo findings of increased intracortical myelin content [24–26] and disorganized myeloarchitecture [24, 27] in AD patients compared to normal controls. The studies have further noted a visibly inhomogeneous band of hypointense T2*‐weighted MRI signals across the cortex, which blurred the cortical laminae and was highly associated with myelin content.…”
Section: Discussionsupporting
confidence: 83%
“…At the mean age of our homozygote group (55 years), approximately 50% of these individuals display abnormal levels of amyloid biomarkers, as compared with only 10% of non-carriers and about 20% of carriers of a single ε4 allele (Jansen et al, 2015). Besides, T1w/T2w ratio might show a positive association with Aβ accumulation (Bartzokis et al, 2007), according to recent results (Yasuno et al, 2017; Pelkmans et al, 2019). Still, such impact, as it was suggested, would come in a direction contrary to the one we find for the APOE-ε4 status, therefore pinpointing the strength of the effect in our dataset regardless of the possible underlying amyloid charge.…”
Section: Discussionmentioning
confidence: 57%
“…It was initially proposed for cortical mapping of myelin, then was extended to the whole brain (Ganzetti et al, 2014) and met a variety of applications with special emphasis in developmental studies (Lee et al, 2015; Soun et al, 2017; Lebel and Deoni, 2018), neurodegenerative diseases e.g. MS (Righart et al, 2017), schizophrenia (Iwatani et al, 2015), Alzheimer's disease (Yasuno et al, 2017; Pelkmans et al, 2019) and the healthy brain (Shafee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the ratio between the signal intensity of the T1- and T2-weighted images is known to reflect cortical myelin content 32 . A recent study has shown that cortical T1/T2 signal intensity ratio significantly differed between AD patients and normal controls 33 . Although we did not include the T1-weighted and T2 FLAIR signal intensity ratio, including features from both sequences might have increased the ability of the prediction model to reflect the microstructural alterations more accurately.…”
Section: Discussionmentioning
confidence: 99%